Decline of cellular activation in non‐B cells after rituximab treatment in hepatitis C‐associated mixed cryoglobulinemia vasculitis. Issue 2 (25th September 2016) - Emmanuel, B.; Sidique, N.; Zhang, X.; Poonia, B.; Sneller, M. C.; Kottilil, S.
Summary: Mixed cryoglobulinemic vasculitis is associated with the monoclonal expansion of pathognomonic B cells in chronic hepatitis C. Recently, treatment with B‐cell depletion, including rituximab, a CD20 monoclonal antibody, has been successful in achieving remission from the active disease. We investigated whether B‐cell depletion therapy has an impact on activation of non‐B cells in the periphery. Results demonstrated that B‐cell depletion therapy is associated with a statistically significant decline in activated T cells, from pretherapy to follow‐up while on rituximab therapy: CD4+ CD38+ HLA‐DR+ (DR+), CD8+ CD38, CD8+ CD38+ DR+, and CD8+ DR+. Birmingham Vasculitis Activity Score and cryoglobulin had a strong correlation coefficient ( R ) of 0.72 ( P =.0005), while cryoglobulin showed moderate correlation with CD8+ DR+ ( R =.61), CD3+ CD38+ DR+ ( R =.57), CD3+ DR+ ( R =.50), CD4+ CD38+ DR+ ( R =.53), CD4+ DR+ ( R =.52), and CD8+ CD38+ DR+ ( R =.67). These results suggest B‐cell expansion has a direct and indirect effect on the pathogenesis of Hepatitis C‐associated mixed cryoglobulinemic vasculitis.